2019
DOI: 10.1556/1326.2018.00459
|View full text |Cite
|
Sign up to set email alerts
|

Determination and pharmacokinetics and bioavailability of O-demethyl nuciferine in mice by UPLC–MS/MS

Abstract: In this study, a precise, rapid, and accurate ultra-performance liquid chromatography-tandem mass spectrometer (UPLC-MS/MS) method for the quantitation of O-demethyl nuciferine in mouse blood was developed, and pharmacokinetics of O-demethyl nuciferine was studied for the first time after sublingual injection and gavage. The study was performed with an UPLC ethylene bridged hybrid (UPLC BEH) (2.1 mm × 50 mm, 1.7 μm) column at 30°C, using diazepam as the internal standard (IS). The mobile phase consisted of ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The liquid chromatography conditions should be chosen in order to effectively separate endogenous interfering substances [ 27 – 29 ] from ropivacaine, 3-hydroxy ropivacaine, and internal standard. During the method development, a series of mobile phases were examined and compared: methanol or acetonitrile (containing 0.1% formic acid), 10 mmol/L ammonium acetate buffer solution (containing 0.1% formic acid) in acetonitrile or methanol, and 10 mmol/L ammonium acetate buffer solution (containing 0.05% ammonia) in methanol or acetonitrile.…”
Section: Resultsmentioning
confidence: 99%
“…The liquid chromatography conditions should be chosen in order to effectively separate endogenous interfering substances [ 27 – 29 ] from ropivacaine, 3-hydroxy ropivacaine, and internal standard. During the method development, a series of mobile phases were examined and compared: methanol or acetonitrile (containing 0.1% formic acid), 10 mmol/L ammonium acetate buffer solution (containing 0.1% formic acid) in acetonitrile or methanol, and 10 mmol/L ammonium acetate buffer solution (containing 0.05% ammonia) in methanol or acetonitrile.…”
Section: Resultsmentioning
confidence: 99%
“…The lower bioavailability of liensinine was further confirmed by the research of Tong et al (2021). A pharmacokinetic study on O-demethyl nuciferine showed that its bioavailability was 6.4% following sublingual injection and gavage (Wu et al 2019). Generally, the poor solubility of alkaloids in lotus, including neferine, higenamine, nunciferine, and N-nunciferine leads to their relatively low in vivo bioavailability (Table 2), thereby limiting their further clinical application.…”
Section: Bioavailabilitymentioning
confidence: 89%